2000
DOI: 10.1097/00042752-200001000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Concussions During the 1997 Canadian Football League Season

Abstract: Many players experienced a concussion during the 1997 CFL season, but the majority of these players may not have recognized that fact. Players need to be better informed about the symptoms and effects of concussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 31 publications
3
82
1
Order By: Relevance
“…Symptoms may be subtle, resemble other conditions such as dehydration and heat exhaustion, or resolve in less than 15 minutes or appear a few days later. [23][24][25] We also observed that consequences such as brain hemorrhage, coma, and death were not identified by more than 30% of participants, suggesting that more education should be directed toward those consequences and risks associated with concussions. Although we did not (19) assess them in our study, other factors that may influence knowledge about concussion are age and level of competition.…”
Section: Discussionmentioning
confidence: 82%
“…Symptoms may be subtle, resemble other conditions such as dehydration and heat exhaustion, or resolve in less than 15 minutes or appear a few days later. [23][24][25] We also observed that consequences such as brain hemorrhage, coma, and death were not identified by more than 30% of participants, suggesting that more education should be directed toward those consequences and risks associated with concussions. Although we did not (19) assess them in our study, other factors that may influence knowledge about concussion are age and level of competition.…”
Section: Discussionmentioning
confidence: 82%
“…The majority of prior studies depended on either the retrospective self-reporting of the athlete, or the judgment of a certified team trainer or first responder. 6,7,11,14,15,18,22,31 Second, the elevated and multisite points of observation used in our study provided improved ability to view the events occurring on the ice surface. Because our observers were specifically looking for concussions prospectively, as opposed to collecting these retrospectively or using historical injury data previously collected, we likely observed and recorded more events than otherwise might have been detected by team staff who have a multitude of other duties.…”
Section: Discussionmentioning
confidence: 99%
“…23 Studies using clinical data (e.g., self-report or athletic trainer examination) have consistently found differences in concussion incidence across football player positions. [30][31][32][33][34][35][36][37] For example, using athlete self-report of concussion symptoms, Guskiewicz and colleagues found that linebackers and offensive linemen had the highest concussion rates per 1000 athletic exposures (AEs; exposure to a game or practice). 30 Based on self-report of concussion or postimpact symptoms, Delaney and colleagues found that tight ends and defensive linemen had the highest rates of diagnosed concussions in college football.…”
mentioning
confidence: 99%
“…31 In an earlier study, Delaney and colleagues found that, in professional football, the highest incidence of concussion was among quarterbacks and running backs. 32 Pellman and colleagues utilized athletic trainer and team physician reports of concussion and indicated that, although defensive backs had the highest incidence of concussions in the National Football League (NFL), quarterbacks had the greatest risk of injury per 100 game AEs. 34 Other studies have combined clinically observed concussions with helmet sensorbased head impact data to generate concussion risk curves, including positional variation.…”
mentioning
confidence: 99%